Vitamin D Promotes Pneumococcal Killing and Modulates Inflammatory Responses in Primary Human Neutrophils - Subramanian, Karthik (J Innate Immun, 2017)
Streptococcus pneumoniae is a major human pathogen and a leading cause of pneumonia, septicemia, and meningitis worldwide. Despite clinical studies linking vitamin D deficiency and pneumonia, molecular mechanisms behind these observations remain unclear. In particular, the effects of vitamin D on neutrophil responses remain unknown. Using pneumococcal strains, primary neutrophils isolated from human blood, and sera from patients with frequent respiratory tract infections (RTIs), we investigated the effects of vitamin D on neutrophil bactericidal and inflammatory responses, including pattern recognition receptors, antimicrobial peptides, and cytokine regulation. We found that vitamin D upregulated pattern recognition receptors, TLR2, and NOD2, and induced the antimicrobial human neutrophil peptides (HNP1–3) and LL-37, resulting in increased killing of pneumococci in a vitamin D receptor-dependent manner. Antibodies targeting HNP1–3 inhibited bacterial killing. Vitamin D supplementation of serum from patients with bacterial RTIs enhanced neutrophil killing. Moreover, vitamin D lowered inflammatory cytokine production by infected neutrophils via IL-4 production and the induction of suppressor of cytokine signaling (SOCS) proteins SOCS-1 and SOCS-3, leading to the suppression of NF-κB signaling. Thus, vitamin D enhances neutrophil killing of S. pneumoniae while dampening excessive inflammatory responses and apoptosis, suggesting that vitamin D could be used alongside antibiotics when treating pneumococcal infections.